THE PRECAUTIONARY PRINCIPLE IN A WORLD OF DIGITAL DEPENDENCIES. - Pieters, Wolter; Cleeff, André van (Computer (00189162), 2009)
The article argues that as systems and organizations become deperimeterized, software engineers could no longer rely on an ethics of consequences but would need a new paradigm in software engineering ethics. It encourages engineers to instead rely on the precautionary principle, which lets them focus on creating a more extensive moral framework. The article further argues that the precautionary principle should be applied to software design so that potentially harmful uses are discouraged and beneficial uses are encouraged. The approach was developed to help cope with problems that arise where there is no longer any digital fence surrounding organizations to protect their security.